Tax Avoidance: The Effect of Political Connection and Institutional Ownership - Breverdy Manihuruk; Santi Novita (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2023)
This study aims to test the effect of institutional ownership and political connection on tax avoidance. This study comprises 836 observations of firms in the non-financial industries from 2015-2018 listed on the Indonesia Stock Exchange. Multiple linear regression analysis with STATA 14 software is used. The result shows that political connections can be a tool to reduce tax avoidance, while institutional ownership effect tax avoidance only in the non-mining industry. The mining industry need wider pressure to mitigate the non-compliance on tax. The research may provide a deep insight the role of political connection especially for fiscal authority. It is a strengthen factor in the relation of the ownership and tax compliance. Furthermore, the character of industry doesn’t indicate that the certain industry has a higher potential to do incompliance